Ronald Reagan’s 1984 - Cooper, James. author. aut Link
X, 107 p. 6 illus., 5 illus. in color.
Keywords: ‘A very fine, insightful and original analysis that uses Ronald Reagan's landslide re-election year as the lens through which to explore American politics, society and culture in the 1980s. This very engaging, accessible, and well written volume is highly recommended for students of US History and American Studies.’ — Iwan Morgan, Emeritus professor of US Studies at University College London and author of Reagan: American Icon Forty years after Ronald Reagan’s successful re-election campaign, this book explores the significance of the year 1984 in the making of Reagan’s presidential record and the shaping of his legacy. The authors examine the broader context of how Reagan impacted the nature of the US presidency and international relations during the Cold War, and how this in turn interacted with American popular culture. Serving as an introduction to academics, students and the interested public into what is a rapidly increasingly Reagan scholarship, this book will also appeal to anyone interested in US elections, the evolving nature of the US presidency, and American culture more generally. James Cooper is an Associate Professor of History and American Studies at York St John University, in the UK. He was previously a Senior Lecturer in History at Oxford Brookes University, UK, and the twentieth Fulbright-Robertson Visiting Professor of British History at Westminster College, Missouri, USA. In May 2016, James was a Visiting Fellow at the Norwegian Nobel Institute. R. J. Richardson is a Postgraduate Researcher at York St John University in the UK. Her thesis explores the concept of authenticity in historically-set, long-form drama, through the creation and analysis of the opening season of a series set in New York City in 1945 Bailey Schwab is a Postgraduate Researcher at York St John University, in the UK, undertaking a thesis in presidential history between 1981 and 2009. His research explores the concept of foreign policy doctrine and how it is utilised in the critique of presidential leadership in foreign policy. .